ORIGINAL PAPERSome specific traits of clinical course of low back pains caused by lumbar discopathy in patients with obesity - Gasik, Robert; Styczyński, Tadeusz (Reumatologia/Rheumatology, 2005)
The aim of this study was to evaluate the course of low back pains in patients with obesity. The material of the study was 152 patients. The BMI (body mass index) was calculated in the group of men and women. The classification was created by considering 30 as BMI boundary value. The patients were examined neurologically and the functional condition of the spine was evaluated. The lumbar lordosis angle and the angle of sacral bone forward inclination was measured on the basis of radiographs of the lumbar spine section. The obesity symptoms in the examined material were determined in 36 patients (23% of the whole group). Overweight, which corresponds to BMI of 25 and over, was determined in 105 patients (69%). By comparing the collected information it was found that spine pain complaints before hospitalisation lasted on average 108.6 months among obese patients and 157.6 months among others. Duration of individual recurrences of back pains in the group of obese patients was in fact statistically shorter and the difference amounted to 1.02 months. Familial occurrence of back pains was determined among 56.9% patients in the Ist group (>30 BMI), and 32.1 in the group of obese patients correspondingly. 41%, 58% and 1% patients in the group of obese patients had elementary, secondary and higher education respectively. 17%, 66% and 17% patients in the first group respectively. Statistical significance was received for the groups with elementary and higher education. The significant differences in anthropometrical measurements were received among the examined patients. The angle of sacral bone forward inclination was 26.89 degrees in the group of obese patients, and 35.6 degrees in the first group. Differences were also found in the lumbar lordosis angle. The angle was 25.95 degrees in the group of patients with BMI of over 30, and 38.89 degrees in the first group of patients. The results show influence of obesity on the course of low back pains caused by lumbar discopathy.